2013
DOI: 10.1002/jhm.2133
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with joint commission measures in state-designated stroke centers

Abstract: BACKGROUND Comparison of state‐designated primary and comprehensive stroke centers (PSCs and CSCs) with regard to adherence to nationally accepted performance standards are scarce. The objective of this study was to examine if a significant association exists between level of designation and fulfillment of Joint Commission (JC) stroke core measures. METHODS A retrospective comparative data analysis of the New Jersey acute stroke registry for the calendar years 2010 and 2011 was performed. JC core measures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Panezai et al. () showed that New Jersey CSC designation compared to PSC was associated with shorter process times and twice the proportion of eligible patients receiving thrombolysis. This analysis was limited by implementation of PSC designation after data collection had begun, whereas CSC designation was already established.…”
Section: Resultsmentioning
confidence: 99%
“…Panezai et al. () showed that New Jersey CSC designation compared to PSC was associated with shorter process times and twice the proportion of eligible patients receiving thrombolysis. This analysis was limited by implementation of PSC designation after data collection had begun, whereas CSC designation was already established.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] In the state of New Jersey as an example, 60% of stroke admissions were at a primary stroke center as compared to 40% at a comprehensive center. [ 21 ] As with carotid stenting, an increase in procedures for large vessel occlusions in thrombectomy-capable low-volume centers is probable with the anticipated increase in procedural volume.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, many academic and community medical centers have sought to establish CSCs. Retrospective analysis has suggested that patient outcomes are improved when stroke care is organized into such centers [11,12,13,14]. For example, Kim et al [15] calculated a 28% reduction in 30-day mortality after establishment of a CSC.…”
Section: Discussionmentioning
confidence: 99%